Manifestasi Empati Dan Kemanusiaan Dalam Dinamika Interaksi Takashi Natsume Dalam Anime Natsume Yuojinchou “Season 1” - Skiara, Mohammad Zen; Saguni, Fatimah; BA, Saude; Anirah, Andi (KIRYOKU, 2026)
Empathy and human values are fundamental to ethical social relations, yet their representation in popular culture, particularly anime, remains underexplored. This study analyzes the manifestation of empathy and human values in the interaction dynamics of Takashi Natsume in Natsume Youjinchou Season 1. Using a qualitative descriptive approach and narrative analysis, the study applies theories of cognitive and affective empathy (Batson & Decety), altruism (Myers), multidimensional tolerance (Hjerm), human dignity (Ferdynus), and moral agency (Vriens et al.). The findings show that Natsume’s empathy is reflected in sensitivity to others’ suffering, voluntary care, acceptance of difference, respect for dignity, and moral responsibility in safeguarding the Book of Friends. Empathy is thus positioned as a relational moral practice that underlies moral agency and a non-human-centered conception of humanity within the narrative.